Public Administration: Research Strategies, concepts and Method - Peters, B. Guy (New York Routledge, 2016)
The book functions as an introduction to central themes of public administration and related traditions of research, but also proposes a new pluralist approach for studying public institutions.
Keywords: Erkkila, Tero; Maravic, Patrick Von; Public Administration